2023
DOI: 10.3762/bjoc.19.119
|View full text |Cite
|
Sign up to set email alerts
|

A series of perylene diimide cathode interlayer materials for green solvent processing in conventional organic photovoltaics

Kathryn M Wolfe,
Shahidul Alam,
Eva German
et al.

Abstract: Herein, we report on the design, synthesis, physical and chemical properties, and organic photovoltaic (OPV) device performance of four new cathode interlayer (CIL) materials based on bay N-annulated perylene diimides. Starting from the previously reported N-annulated perylene diimide (PDIN-H), the N-position was functionalized with a benzyl and pentafluorobenzyl group to make PDIN-B and PDIN-FB, respectively. Similarly, starting from the previously reported cyanated N-annulated perylene diimide (CN-PDIN-H), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…These challenges require novel approaches but there have already been some inspired works. For example, Wolfe et al showed cathode interlayer materials can be developed to be soluble in ethyl acetate, a green solvent, and solution-processed for PM6:Y6 bulk-heterojunction solar cells with power conversion efficiency > 13% [ 6 ]. In addition to orthogonal processing, it has been shown that treatment with base [ 7 ] or photo-crosslinking [ 8 ] can insolubilise solution-processed layers and allow for the construction of efficient, solution-processed devices.…”
mentioning
confidence: 99%
“…These challenges require novel approaches but there have already been some inspired works. For example, Wolfe et al showed cathode interlayer materials can be developed to be soluble in ethyl acetate, a green solvent, and solution-processed for PM6:Y6 bulk-heterojunction solar cells with power conversion efficiency > 13% [ 6 ]. In addition to orthogonal processing, it has been shown that treatment with base [ 7 ] or photo-crosslinking [ 8 ] can insolubilise solution-processed layers and allow for the construction of efficient, solution-processed devices.…”
mentioning
confidence: 99%